The Two-Way Relationship of Tradition and Quality - Zachariadis, Angelos (Technical Annals, 2025)
The term Tradition refers to all those elements that are handed down from one generation to another in the cycles of life, and the term Quality refers to all those that make the cycles of life easy and pleasant. Tradition and Quality are elements that existed and exist in all beings of Nature. However, only in humans do these elements operate consciously and not only by instinct. Although it is considered that the human race differentiated itself from the rest of the beings on the Planet when it took an upright position, the essential differentiation occurred when humanity acquired a quality of life with the creation of civilization. Tradition in the human race was recorded in the past with its Myths and History, and today History is complemented by the findings of Astrologers and Paleontologists. Thus, we would say that today Tradition concerns all those findings from the creation of the Universe to the future. The analysis of life cycles from the creation of the Universe to the present day presents a continuous repetition of beginning, growth, peak, decline and end. These “Life Cycles” are in this way standartized, and are influenced by random events that cause disasters that overturn the order of succession or break them up. In the standardization of Life Cycles, disasters are scientifically classified into "Natural" and "Endemic". When the end was definitive for the beings of the Planet, they disappeared, and in the History of some peoples of the human race the end was definitive and they disappeared. For some other peoples, though, a new beginning followed after the end, and these peoples survived. In all beings, their survival depends on the ability to adapt to changes in their environment. In the History of the human race as well, their peak was identical to their civilization. Of all the human developed civilizations, only the civilization of the Greeks, which emerged from the socio-economic system of Democracy, has survived to this day. After the Industrial Revolution, tradition was displaced in the human race by Technology and today the protypes, that were handed down from one human generation to the next, have been replaced by the industrial standards. Although today, at the end of the Industrial Age, the standards have been evolved with the "Quality Systems", they continue, with the dominance of Technology, tο lead the human race to destruction and extinction. The Balkans, which share the tradition of the Ancient Greek Civilization and have not yet been industrialized, are the exception to this rule. Here in the Balkans the “Post-Traditional” human civilization can be developed, and thus the Balkan peoples will help the human race to survive, reach its peak and remain there during the Post-Industrial Age.